2017
DOI: 10.1007/s41748-017-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical and Geochemical Assessments of Shales in Anambra Basin, Southeastern Nigeria, as Landfill Liners

Abstract: Background The use of landfills as containment for municipal solid waste management has received wide acceptance the world over. Its development in countries like Nigeria is constrained by high cost and scarcity of synthetic liners in the local markets. Exploration of the abundant locally available clay deposits in the country's sedimentary Basins will prove economical, provided it satisfies the standard specifications for design and construction of landfill liners. Purpose This study thus evaluates the suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The predominant soil type underlying the problematic engineering structures in the present study area is clay belonging to the Awgu Shale group in the Anambra Basin. Among all tested expansive clay units (Asu-River, Imo, Enugu and Nkporo formations) underlying the Anambra Basin, Awgu Shale exhibited the highest expansive nature and consequently, lower strength characteristics (Adesina et al 2012;Ekeocha 2014). Aghamelu et al (2011a) suggested that the conversion of high expansive clay into less expansive types could be the reason for lower plasticity index of the Imo Shale.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant soil type underlying the problematic engineering structures in the present study area is clay belonging to the Awgu Shale group in the Anambra Basin. Among all tested expansive clay units (Asu-River, Imo, Enugu and Nkporo formations) underlying the Anambra Basin, Awgu Shale exhibited the highest expansive nature and consequently, lower strength characteristics (Adesina et al 2012;Ekeocha 2014). Aghamelu et al (2011a) suggested that the conversion of high expansive clay into less expansive types could be the reason for lower plasticity index of the Imo Shale.…”
Section: Introductionmentioning
confidence: 99%
“…Landfills are covered with liners or covered with an underlayment to lessen the issues caused by leachate coming into touch with groundwater. In most cases, liners consist of a bottom liner, a geosynthetic clay liner (GCL), a geological barrier, and compacted clay and geomembrane (Declan and Paul, 2003;Leite et al, 2003;Frempong and Yanful, 2008;Budihardjo, 2015;Adesina and Tijani, 2017). According to Adesina and Tijani (2017), shales and other geologic materials have also been used as landfill liners.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, liners consist of a bottom liner, a geosynthetic clay liner (GCL), a geological barrier, and compacted clay and geomembrane (Declan and Paul, 2003;Leite et al, 2003;Frempong and Yanful, 2008;Budihardjo, 2015;Adesina and Tijani, 2017). According to Adesina and Tijani (2017), shales and other geologic materials have also been used as landfill liners. These materials have demonstrated their suitability by effectively combating the soil and groundwater contamination often associated with waste management techniques (Adesina and Tijani, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okogbue et al (2010) compared geotechnical properties of Abakaliki, Awgu and Enugu shale formations and their likely use for construction and suggested that Abakaliki shale may be satisfactory as fill and embankment material but may not be good as sub base material due to high liquid limit and plasticity index. Adeshina et al (2017) studied shales (Enugu, Ameki and Imo) in Anambra Basin for use as landfill liners and suggested that high hydraulic conductivity and swelling potentials of the shales would not make them suitable for natural clay liners. These aspects of research, however, have not been *Corresponding Author extended to the shales and claystone in the southern Bida Basin despite its substantial occurrence both in the subsurface and outcrop levels.…”
Section: Introductionmentioning
confidence: 99%